Behavior Evaluation of Ultrahigh-Performance Concrete Beam Containing Para-Aramid Fibers. (20th May 2019) - Kim, Seung-Ki; Kim, Woosuk; Han, Sang-Mook
Abstract : This experimental research was performed to evaluate the shear and flexural behavior for two cases of reinforced concrete beams: ultrahigh-performance concrete (UHPC) and normal-strength concrete jacketed with UHPC. The experiment was performed to examine the optimum para-aramid fiber to reinforce the ductile UHPC, with the test variables fiber diameter and length. Beam tests were then performed to evaluate the performance of the UHPC and jacketed beams. The UHPC beam tests with and without stirrups were conducted to evaluate flexural and shear behavior, respectively. The beam tests with and without jacketing were conducted to evaluate the reinforcement performance of UHPC.